ANALYSIS OF PULMONARY FUNCTION IN PATIENTS WITH SEVERE OBESITY INDICATED FOR BARIATRIC SURGERY: A LITERATURE REVIEW (CIPEEX, 2025)
Introduction: Obesity is a chronic disease characterized by excessive accumulation of body fat, which causes significant harm to the individual. This condition has reached epidemic proportions, becoming a global health problem with increasing prevalence in recent years, and is the most frequent metabolic disorder. The surgical procedure most commonly used for the treatment of morbid obesity is bariatric surgery, with variations depending on the techniques employed. Objective: To identify the correlation between obesity and its effects on pulmonary function, ventilatory pressure, and mechanics, with a focus on the influence of bariatric surgery on patients’ functional recovery. Methodology: Articles were collected from databases such as PubMed, Google Scholar, and SciELO, published between 2010 and 2024, using Health Sciences Descriptors (DeCS): “severe obesity,” “bariatric surgery,” and “pulmonary function.” Inclusion criteria were clinical trials, published in any language and with free access, that addressed the topic. Exclusion criteria included incomplete studies and those with missing data. Results: Correlations were observed between obesity and worsening pulmonary function in obese patients, with reductions in vital capacity (VC) and functional residual capacity (FRC), as well as improvements in parameters such as forced expiratory volume in the first second (FEV1) and forced vital capacity (FVC) after bariatric surgery and subsequent weight loss. Conclusion: The analyzed studies demonstrate a negative relationship between obesity and pulmonary function, particularly in morbidly obese patients indicated for surgery, where significant ventilatory impairment is present.
Keywords: Severe obesity; Bariatric surgery; Pulmonary function